Effect of different light curing units on Knoop hardness and temperature of resin composite - Guiraldo Ricardo; Consani Simonides; Xediek Consani Rafael; Mendes Wilson; Lympius Thais; Coelho Sinhoreti Mario (Wolters Kluwer Medknow Publications, 2009)
Aim: To evaluate the influence of quartz tungsten halogen and plasma arc curing (PAC) lights on Knoop hardness and change in polymerization temperature of resin composite. Materials and Methods: Filtek Z250 and Esthet X composites were used in the shade A3. The temperature increase was registered with Type-k thermocouple connected to a digital thermometer (Iopetherm 46). A self-cured polymerized acrylic resin base was built in order to guide the thermocouple and to support the dentin disk of 1.0 mm thickness obtained from bovine tooth. On the acrylic resin base, elastomer mold of 2.0 mm was adapted. The temperature increase was measured after composite light curing. After 24 h, the specimens were submitted to Knoop hardness test (HMV-2000, Shimadzu, Tokyo, Japan). Data were submitted to ANOVA and Tukey′s test (a = 0.05). Results: For both composites, there were no significant differences (P > 0.05) in the top surface hardness; however, PAC promoted statistically lower (P < 0.05) Knoop hardness number values in the bottom. The mean temperature increase showed no significant statistical differences (P > 0.05). Conclusion: The standardized radiant exposure showed no influence on the temperature increase of the composite, however, showed significant effect on hardness values.